Evaluasi Performa Keuangan dengan Du Pont System dan EVA PT Matahari Putra Prima Tbk - Dian Apriliani; Ade Ali Nurdin; Dimas Sumitra Danisworo (Indonesian Journal of Economics and Management, 2021)
The level of sales of Indonesian retail industry decreased, this research aims to determine financial performance using the Du Pont System and EVA approach in PT Matahari Putra Prima Ltd period 2015-2019, to determine the effectivity and efficiency as well as the ability to create value added for company. The research method used quantitative descriptive method using secondary data obtained from the Company’s official website, in the form of the financial statements of PT Matahari Putra Prima Ltd period 2015-2019. The result show the value of ROA and ROE there is fluctuation and have negative value on 2017-2019, this show that the company get a profit decline and below the industry standar average. That is show the Company less effectiveness in manage assets and control expense incurred by Company. The Value Added of Campany not created on 2015 but on 2016-2019 Company able to create value added.